Hepatitis B on Pregnant Women in Daerah Khusus Ibukota (DKI) Jakarta 2015 - ., Yusnabeti; Priyo Hastono, S (KnE Life Sciences, 2019)
The Hepatitis B virus has infected some 2 billion people in the world. Indonesia is the second largest in the South East Asian Region (SEAR) after Myanmar. According to the results of Riskesdas in 2013, the number of people diagnosed by symptoms, showed twice increase compared to 2007 data. The effect of hepatitis virus on pregnant women increase the incidence of abortion, parts premiums, and bleeding. Risks to the fetus are premature, fetal death and transmission of viral hepatitis. This study aimed to determine the prevalence of hepatitis B in pregnant women in Daerah Khusus Ibukota (DKI) Jakarta (except the Kepulauan Seribu) in 2015. The data obtained from Sub-directorate of Hepatitis and Gastrointestinal Infectious Diseases Directorate General of Disease Prevention and Control Ministry of Health of the Republic of Indonesia as the institution that has the Hepatitis B survey program in 2015 in collaborated to Dinas Kesehatan (public health Office) and Puskesmas (community Health centers) in five areas of DKI Jakarta and BBLK Jakarta as laboratory inspectors. As the result of the research, known that Hepatitis B sufferers in pregnant women as much as three people per 100.000 population (2.76/100.000) with 95% confidence interval, this number increased compared to 2014 that there were two people per 100.000 population (1.66/100.000). The proportion of pregnant women suffering from Hepatitis B in 2015 was 2.12%, increasing from the previous year which amounted to 1.98%. From the five areas of DKI Jakarta, the highest proportion occurred in North Jakarta at 2.57%, while the lowest was in South Jakarta at 1.65%. Hepatitis B infection plays an essential role in the occurrence of chronic liver disease in Indonesia. The preventing and omitting the transmission chains especially from pregnant women can further enhance through the part of the government and individual communities. Keywords: hepatitis B, pregnant women, DKI Jakarta, prevalence.